Annealing effects on fracture process and tensile strength of non-combustible Mg products fabricated by selective laser melting. (August 2022) - Proaño, Bryan; Miyahara, Hirofumi; Morishita, Kohei; Matsumoto, Toshiharu; Sakai, Hitoshi; Noguchi, Hiroshi; Hamada, Shigeru
Highlights: Mg-9%Al-2%Ca alloy specimens were fabricated using selective laser melting. SLM products contain two phases, viz., coarse and fine microstructures. Annealing dissipates coarse microstructure and enables dislocations move freely. For annealed products strength cannot be predicted by fracture toughness value. R -curve application validity for annealed specimen were discussed. Abstract: This study systematically investigates the effects of annealing heat treatment on the microstructure, plastic strain manifestation, and the consequent fracture process in products fabricated via selective laser melting (SLM). Several Mg-9%Al-2%Ca alloy round bars and cubic specimens were fabricated and heat-treated subsequently. The round bar specimens were subjected to tensile testing and subsequent fracture surface and electron backscatter diffraction analyses for the observation of plastic strain. The microstructural and microhardness analyses of the cut cubic specimens showed that the coarse microstructure at the melt pool borders dissipated owing to the annealing effect, and the overall hardness of the material was significantly reduced. Consequently, when tensile stresses were applied, stable crack propagation was enabled by microstructure homogenization instead of the sudden interruption of propagation, a phenomenon exclusively responsible for fracture under as-built conditions. Accordingly, the annealed specimens showed an increase in ductility but a reduction in the ultimate tensile strength. Furthermore, the fracture toughness value, which is a critical parameter used to predict unstable fractures under as-built conditions, can no longer be considered for the annealed specimens due to the elimination of the crack propagation interruption. Therefore, this study discusses the validity of applying an R -curve. Accordingly, a concrete analysis of the fracture process in annealed specimens can provide valuable insights for determining the conditions under which annealing would be an optimal process for the end product.